Service Abstractions With Fault Virtualization for Distributed Network Infrastructures - Ravindran, Kaliappa; Jun Wu; Adiththan, Arun (2013 IEEE/ACM 17th International Symposium on Distributed Simulation and Real Time Applications, 2013)
The paper deals with service abstractions that allow managing the dependability features of networked application systems.Component-level faults in the infrastructure are mapped on to degradations in the service quality space. Fault recovery mechanisms in a service-layer algorithm, if any, purport to maintain either the same level of service as in the no-fault case or a reduced level of service proportionate to the fault severity. Treating the occurrence of component faults as a normal case rather than as an exception, a virtualization mechanism provides a systematic mapping of faults on to canonical service quality spaces in a measurable way (e.g.,service availability and agility). Our paper describes the generic mechanisms and programming interfaces in the virtualization layer to manage the infrastructure in a flexible way that allows attaining an optimal service quality. Such service layer abstractions are useful for applications to in fuse adaptive fault-tolerance and quality assurance.